Inactivation of human pancreatic ductal adenocarcinoma with atmospheric plasma treated media and water: a comparative study. (4th June 2018) - Kumar, Naresh; Attri, Pankaj; Dewilde, Sylvia; Bogaerts, Annemie
Abstract: In recent years, the interest in treating cancer cells with plasma treated media (PTM) and plasma treated water (PTW) has increased tremendously. However, the actions of PTM and PTW are still not entirely understood. For instance, it is not clear whether the action of PTM is due to a modification in proteins/amino acids after plasma treatment of the media, or due to reactive oxygen and nitrogen species (RONS) generated from the plasma, or a combination of both effects. To differentiate between the actions of RONS and modified proteins/amino acids on the treatment of cancer cells, we compared the effects of PTM and PTW on two different pancreatic ductal adenocarcinomas (MiaPaca-2, BxPc3) and pancreatic stellate cells (PSCs) (hPSC128-SV). PSCs closely interact with cancer cells to create a tumor-promoting environment that stimulates local tumor progression and metastasis. We treated culture media and deionized water with a cold atmospheric plasma (CAP) jet, and subsequently applied this PTM/PTW at various ratios to the pancreatic cancer and PSC cell lines. We evaluated cell death, intracellular ROS concentrations and the mRNA expression profiles of four oxidative stress-related genes, i.e. Mitogen-activated protein kinase 7 (MAPK7), B-cell lymphoma 2 (BCL2), Checkpoint kinase 1 (CHEK1) and DNA damage-inducible transcript 3, also known as C/EBP homologous protein (CHOP). Our findings demonstrate that PTM and PTW have a similar efficacy to kill pancreatic cancer cells, while PTW is slightly more effective in killing PSCs, as compared to PTM. Furthermore, we observed an enhancement of the intracellular ROS concentrations in both pancreatic cancer cells and PSCs. Thus, it is likely that under our experimental conditions, the anti-cancer activity of PTM can be attributed more to the RONS present in the treated liquid, than to the modification of proteins/amino acids in the media. Furthermore, the fact that the chemo-resistant PSCs were killed by PTM/PTW may offer possibilities for new anti-cancer therapies for pancreatic cancer cells, including PSCs.